Guided Discovery Learning And Fraction Puzzles Facilitate Mathematical Comprehension For Slow Learners: Pembelajaran Penemuan Terbimbing Dan Teka Teki Pecahan Memfasilitasi Pemahaman Matematis Siswa Lamban Belajar - Jumiri Aziz; Siti Rohmah Nurhayati (Academia Open, 2026)
General Background Primary education establishes foundational mathematical competencies necessary for logical reasoning and quantitative literacy. Specific Background Students at risk of being slow learners often struggle with abstract mathematical topics, particularly proportional quantities, due to limited working memory capacity and slower cognitive processing speeds. Knowledge Gap Traditional mathematics instruction predominantly utilizes abstract, lecture-based procedures without sufficient concrete manipulative scaffolding, thereby overwhelming the cognitive load of slower learners. Aims This research investigates the application of a modified guided pedagogical framework supported by physical manipulative media to facilitate mathematical conceptualization in fifth-grade students facing cognitive delays. Results Following a two-cycle adaptive classroom action research methodology, the participants' average conceptual understanding scores progressed from 48.0 to 78.0. Furthermore, classroom mastery rates grew from 0% in the preliminary phase to 100%, alongside notable increases in active participation and independent problem-solving capabilities. Novelty This study uniquely adapts exploratory pedagogical frameworks by integrating visual simplifications and concrete enactive manipulation to specifically accommodate the restricted working memory of slower processing students. Implications Providing structured, hands-on learning experiences offers a practical strategy for educators to minimize extraneous cognitive load and cultivate proportional reasoning in inclusive elementary classrooms. Highlights The modified pedagogical intervention progressed the average participant test scores from 48.0 to 78.0 across two instructional cycles. Classroom mastery rates for proportional reasoning tasks advanced from zero to full attainment following the concrete manipulative integration. Participants demonstrated substantial behavioral transitions from passive observation to active engagement and independent cognitive processing. Keywords Proportional Reasoning; Cognitive Load; Inclusive Classrooms; Concrete Manipulatives; Action Research